Effects of salicylic acid on sucrose synthase activity during seed development and germination in pea (Pisum sativum L.) - Murtaza, Ghulam; Asghar, Rehana (Bangladesh Journal of Botany, 2013)
Effects of 0, 0.1 and 0.01 mM salicylic acid (SA) on activities of sucrose synthase (Sus) in four varieties of pea (Pisum sativum L.) viz., Meteor, Climax, Green feast and Rondo during seed development and germination were studied. Sus activity was highest in the variety Meteor and for the varieties treated with SA (0.1 mM), while the varieties treated twice i.e. seed treated plus foliar spray revealed maximum Sus activity. During germination, the maximum Sus activity was observed for the variety Green feast. Seeds treated with SA 0.1 mM revealed maximum Sus activity, while the seeds raised from the varieties and whose seeds were treated plus foliar sprayed exhibited maximum Sus activity. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15868 Bangladesh J. Bot. 42(1): 83-90, 2013 (June)